2019
DOI: 10.1016/j.esxm.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bupivacaine on the Efficacy of Antibiotic Coating on Penile Implants in Preventing Infection

Abstract: Background:In an effort to reduce dependence on opioids following inflatable penile prosthesis placement, intra-operative soaking of the implant in Bupivacaine (BUP) has been proposed as part of a multimodal approach to pain control. However, no study has shown if the addition of BUP affects the antimicrobial properties of InhibiZone on AMS700 (Boston Scientific, Marlborough, MA) and/or of antibiotic soaked Titan Coloplast (Coloplast Corporation, Minneapolis, MN). Aim: To determine if BUP alters the zone of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Growth of both S epidermidis and E coli at 24 and 48 hours of incubation was inhibited in all implants without any extra bacterial growth promoted by bupivacaine. The authors of this paper indicated that the use of bupivacaine does not affect the protective effects of antibiotic dips and can safely be used during penile prosthesis surgery pending clinical trials (37). This basic science study has been somewhat applied in a clinical fashion during a study performed by Ghanem et al (38).…”
Section: Use Of Bupivacainementioning
confidence: 98%
“…Growth of both S epidermidis and E coli at 24 and 48 hours of incubation was inhibited in all implants without any extra bacterial growth promoted by bupivacaine. The authors of this paper indicated that the use of bupivacaine does not affect the protective effects of antibiotic dips and can safely be used during penile prosthesis surgery pending clinical trials (37). This basic science study has been somewhat applied in a clinical fashion during a study performed by Ghanem et al (38).…”
Section: Use Of Bupivacainementioning
confidence: 98%